Interaction between metabotropic glutamate receptor 7 and alpha tubulin - Saugstad, Julie A. (2002)
Metabotropic glutamate receptors (mGluRs) mediate a variety of responses to glutamate in the central nervous system. A primary role for group-III mGluRs is to inhibit neurotransmitter release from presynaptic terminals, but the molecular mechanisms that regulate presynaptic trafficking and activity of group-III mGluRs are not well understood. Here, we describe the interaction of mGluR7, a group-III mGluR and presynaptic autoreceptor, with the cytoskeletal protein, alpha tubulin. The mGluR7 carboxy terminal (CT) region was expressed as a GST fusion protein and incubated with rat brain extract to purify potential mGluR7-interacting proteins. These studies yielded a single prominent mGluR7 CT-associated protein of 55 kDa, which subsequent microsequencing analysis revealed to be alpha tubulin. Coimmunoprecipitation assays confirmed that full-length mGluR7 and alpha tubulin interact in rat brain as well as in BHK cells stably expressing mGluR7a, a splice variant of mGluR7. In addition, protein overlay experiments showed that the CT domain of mGluR7a binds specifically to purified tubulin and calmodulin, but not to bovine serum albumin. Further pull-down studies revealed that another splice variant mGluR7b also interacts with alpha tubulin, indicating that the binding region is not localized to the splice-variant regions of either mGluR7a (900–915) or mGluR7b (900–923). Indeed, deletion mutagenesis experiments revealed that the alpha tubulin-binding site is located within amino acids 873–892 of the mGluR7 CT domain, a region known to be important for regulation of mGluR7 trafficking. Interestingly, activation of mGluR7a in cells results in an immediate and significant decrease in alpha tubulin binding. These data suggest that the mGluR7/alpha tubulin interaction may provide a mechanism to control access of the CT domain to regulatory molecules, or alternatively, that this interaction may lead to morphological changes in the presynaptic membrane in response to receptor activation.